Effects of Brazing Technology on Hermeticity of Alumina Ceramic-Metal Joint Used in Nuclear Power Plants - Deng, Nengmei; Zhao, Jun; Yang, Lilin; Zheng, Zhiqin (Frontiers in Materials, 2021)
Taking the brazing mechanism of alumina ceramics and kovar alloys as the main research object, based on the molybdenum–manganese metallization method, the influence of the direct and indirect brazing processes on the morphology of the final connected layer is explored. Combined with SEM, EDS, the microscopic morphology, and hermeticity affecting the final ceramic–metal composite component is discussed. Finally, through the indirect brazing process, various ceramic–metal composite joints with good airtightness satisfying the requirements were prepared.